Colonial architecture as heritage: German colonial architecture in post-colonial Windhoek - Ruhlig, Vanessa Jane (Conservation of the Built Environment, 2019)
The rapid post-Independence development of the city of Windhoek, Namibia; and the ensuing destruction of a substantial number of German colonial buildings in the capital city, prompted speculation as to why these buildings are inadequately protected as heritage – and whether they are, in fact, considered to be heritage. The study explores the issues pertaining to the presence of German colonial architecture, as artefacts of the German colonial period, within the postcolonial context of Windhoek. The trauma and pain of the Namibian War and genocide (1904 – 1908) are recurring themes in the body of literature on postcolonial Namibia; and this informs a wider discourse on memory. Memory is found to play a crucial role in evoking a sense of both individual and shared ownership, through its capacity to create meaning, which can in turn ascribe value to a place. Memory is also dependent on visual cues for its continued existence, which suggests the importance of colonial architecture as a material prompt to sustain memory. The research therefore investigates the memories and multiple meanings attributable to colonial architecture in this plural society, and how these meanings can be created, or possibly reinvented, through the continued use of these buildings. The study is based on an assessment of three halls in Windhoek – the Grüner Kranz Hall (1906), the Kaiserkrone Hall (1909), and the Turnhalle (1909; 1912), all designed by the German architect Otto Busch – which illustrates in part, the need for the development of historical building surveys that assess the social values and significances of these contested spaces; and moreover, the potential that these spaces have to support memory work through their continued use.